2022
DOI: 10.32479/ijeep.13154
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Board Structure on Voluntary Environmental and Energy Disclosure in an Emerging Market

Abstract: This study aimed to investigate the effect of board structure on voluntary environmental and energy disclosure of listed firms in Indonesia. The study employed a one-step and two-step system generalized method of moments (GMM) using an unbalanced data panel of 356 non-finance companies. The findings showed that board size positively and significantly affected environmental and energy disclosure. Moreover, board independence negatively and significantly influenced environmental and energy disclosure, while wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Yermack (1996) stated that companies with small boards increased market prices because they paid less compensation and improved CEO performance, which investors saw as a positive signal. Similarly, Amalia et al (2022) found that board size had a positive effect on environmental and energy disclosure, adding value to companies in the capital market. In contrast, Orozco et al (2018) stated that companies with large boards improved company performance and reputation, resulting in increased market value.…”
Section: European Journal Of Management and Business Economicsmentioning
confidence: 94%
“…Yermack (1996) stated that companies with small boards increased market prices because they paid less compensation and improved CEO performance, which investors saw as a positive signal. Similarly, Amalia et al (2022) found that board size had a positive effect on environmental and energy disclosure, adding value to companies in the capital market. In contrast, Orozco et al (2018) stated that companies with large boards improved company performance and reputation, resulting in increased market value.…”
Section: European Journal Of Management and Business Economicsmentioning
confidence: 94%
“…The control variables used include industrial structure (INDS), population growth (POGR), and crisis (CRIS). The industry sector, including construction (INDS), has a significant impact on greenhouse gas emissions, which can be both positive and negative (Mahmoudi et al, 2021;Wei et al, 2007;Lin and Xie, 2014;Gao et al, 2022;Lestari et al, 2022;Amalia et al, 2022;Musviyanti et al, 2022). On the positive side, industrial growth contributes to economic development, job creation, and improved living standards.…”
Section: Methodsmentioning
confidence: 99%